The results of a study on natural fish species at the Da basin, Muong Te district, Lai Chau province - Hoa, Nguyen Thi; Yen, Mai Dinh; Duc, Nguyen Huu (Academia Journal of Biology, 2014)
Muong Te, where The Da river runs into Vietnam, is a mountainous district of Laichau province. It is the higher section of The Da river, with 115 kilometers long and high density of springs. The natural fishes in Muong Te include 63 species which are classified into 36 genera, 14 families, 5 orders. In which, 41, 12 and 6 species, respectively, belong to Cyprinifotmes, Perciformes and Siluriformes, which are given as 66%, 19% and 9%. Synbranchiformes order has three species and Beloniformes order has only one species. 4 species being in Red Data Book of Vietnam (2007) are: Semilabeo obscurus, Sinilabeo tonkinensis tonkinensis, Hemibagrus gustatus, Bagarius rutilus. A species, namely Sinilabeo tetrabarbara, was described by Mai Dinh Yen in 1978 and it hasn’t seen since then. However, 2 samples of that fish have found in Muong Te. The natural fishes in Muong Te have specific features of species of fish living in mountainous and highland regions in North of Vietnam. They are species belong to genaras Glyptothorax, Pseudecheneis, Sinogastromyzon, Balistora, Semilabeo and Sinilabeo. There are 4 species that may be new, they are into genera: Schistura, Mastacembelus, Synogastromyzon. The 3 supplementary species to fishes in The Da river basin (in Lai Chau, Dien Bien, Son La) are: Hemibarbus medius, Hemibarbus lehoai, Sinilabeo tetrabarbara. Fishes of regional fauna in Muong Te (63 species) is much more plentiful than Fishes of Da river in Yunnan, China (27 species ). 37 species of fish living in Muong Te is not seen in both Red river and Da river in Yunnan, China. It is necessary to continue studying components of fishing species in natural Regional fauna in Muong Te district, Lai Chau province. It is helpful to suggess methods for exploiting, preserving and growing reasonably.